Strategic Family Therapy untuk Memperbaiki Komunikasi dalam Keluarga di Nganjuk - Wahyu Utami (Journal An-Nafs: Kajian Penelitian Psikologi, 2017)
Subjects in this case study were family members consisting of mother (52 years), boy (35 years), daughter (30 years), son (32 years) and grandchild (4 years) . Assessment method used is interview, observation and measurement scale. Assessment results indicate that families experience failure in communication patterns, interactions in families rigid and close each other. The intervention used was strategic family therapy in six sessions, aimed at changing communication among family members. The results of the intervention show that each family member becomes more open and there is no misunderstanding among members and there is cooperation in carrying out the responsibilities related to domestic work.